Drop transport and positioning on lubricant-impregnated surfaces. Issue 18 (21st April 2017) - Hui Guan, Jian; Ruiz-Gutiérrez, Élfego; Xu, Ben Bin; Wood, David; McHale, Glen; Ledesma-Aguilar, Rodrigo; George Wells, Gary
Abstract : Achieving droplet self-propulsion and positioning, on lubricant-impregnated surfaces using macro structures to create deformations in a lubricating liquid film. Abstract : We demonstrate the transport and positioning of water droplets on macro-patterned lubricant-impregnated surfaces. The macro-patterning produces menisci features in the impregnating liquid layer which interact with a droplet via a capillary mechanism similar to the Cheerios effect. These interactions control the droplet motion and positioning on an otherwise completely slippery surface. We present experimental results using a V-shape channel geometry as a model system. The interaction between deformations on the lubricant layer induced by the droplet and the underlying V-shape geometry leads to both local and global equilibrium positions for the droplet within the channel. We present a mathematical model to quantify the transition from local equilibrium states to the global equilibrium state and show that the latter can be described on the basis of a force balance along the apparent contact line of the droplet. We highlight possible applications where lubricated macro-patterned surfaces can be used to control the motion and localisation of droplets.